Electronic, Magnetic, and Optical Performances of Non-Metals Doped Silicon Carbide - Zhang, Lin; Cui, Zhen (Frontiers in Chemistry, 2022)
The configurations of nine different non-metals doped silicon carbide (NM-SiC) were structured by using the density functional theory (DFT). The magnetic, electronic, and optical properties of each NM-SiC are investigated at the most stable structure with the maximum binding energy. Although the O-, S-, and Si-SiC systems are still non-magnetic semiconductors, the N- and P-SiC systems have the properties of the magnetic semiconductors. The H-, F-, and Cl-SiC systems exhibit the half-metal behaviors, while the B-SiC system converts to magnetic metals. The redistribution of charges occurs between NM atoms and adjacent C atoms. For the same doping position, the more charges are transferred, the greater the binding energy of the NM-SiC system. The work function of the NM-SiC systems is also adjusted by the doping of NM atoms, and achieves the minimum 3.70 eV in the P-SiC, just 77.1% of the original SiC. The absorption spectrum of the NM-SiC systems occurs red-shift in the ultraviolet light region, accompanying the decrease of absorption coefficient. These adjustable magnetic, electronic, and optical performances of NM-SiC expand the application fields of two-dimensional (2D) SiC, especially in designing field emission and spintronics devices.